Onion: Breeding and Genomics - Mahajan, Vijay; Gupta, Amar J. (Vegetable Science, 2023)
Onion is a long-cultivated vegetable crop that originated in Central Asia. Almost everywhere in the world, onions are cultivated because of their culinary, nutritional, medicinal and health benefits. Using traditional breeding methods, breeders and farmers have been working to enhance onion yield for years. While it is currently difficult to meet growing customer demand and deal with unfavorable climate conditions. Due to its biennial life cycle, cross-pollination and inbreeding depression, it has been challenging to characterize significant traits. Consequently, the recently available onion genome sequence and the use of contemporary molecular breeding techniques will help researchers to overcome those challenges and speed up the development of the onion crop.